Effect of Maximal Apnoea Easy-Going and Struggle Phases on Subarachnoid Width and Pial Artery Pulsation in Elite Breath-Hold Divers - Winklewski, Pawel J. (PLoS One, 2015)
PURPOSE: The aim of the study was to assess changes in subarachnoid space width (sas-TQ), the marker of intracranial pressure (ICP), pial artery pulsation (cc-TQ) and cardiac contribution to blood pressure (BP), cerebral blood flow velocity (CBFV) and cc-TQ oscillations throughout the maximal breath hold in elite apnoea divers. Non-invasive assessment of sas-TQ and cc-TQ became possible due to recently developed method based on infrared radiation, called near-infrared transillumination/backscattering sounding (NIR-T/BSS). METHODS: The experimental group consisted of seven breath-hold divers (six men). During testing, each participant performed a single maximal end-inspiratory breath hold. Apnoea consisted of the easy-going and struggle phases (characterised by involuntary breathing movements (IBMs)). Heart rate (HR) was determined using a standard ECG. BP was assessed using the photoplethysmography method. SaO(2) was monitored continuously with pulse oximetry. A pneumatic chest belt was used to register thoracic and abdominal movements. Cerebral blood flow velocity (CBFV) was estimated by a 2-MHz transcranial Doppler ultrasonic probe. sas-TQ and cc-TQ were measured using NIR-T/BSS. Wavelet transform analysis was performed to assess cardiac contribution to BP, CBFV and cc-TQ oscillations. RESULTS: Mean BP and CBFV increased compared to baseline at the end of the easy phase and were further augmented by IBMs. cc-TQ increased compared to baseline at the end of the easy phase and remained stable during the IBMs. HR did not change significantly throughout the apnoea, although a trend toward a decrease during the easy phase and recovery during the IBMs was visible. Amplitudes of BP, CBFV and cc-TQ were augmented. sas-TQ and SaO(2) decreased at the easy phase of apnoea and further decreased during the IBMs. CONCLUSIONS: Apnoea increases intracranial pressure and pial artery pulsation. Pial artery pulsation seems to be stabilised by the IBMs. Cardiac contribution to BP, CBFV and cc-TQ oscillations does not change throughout the apnoea.